Molecular investigations in date palm genetic structure and diversity among commercially important date palm cultivars (Phoenix dactylifera L.) - Zaid, Salah E., author; Hughes, Harrison, advisor; Krishnan, Sarada, committee member; Brick, Mark, committee member; Davidson, Robert, committee member (Colorado State University. Libraries, 2019)
The date palm, Phoenix dactylifera L. is the notable palm which produces a nutrient-rich edible fruit (the date), well known for its unique attributes of medicine and healthy energy. It is a species that has been cultivated since early civilizations in the fertile crescent and later in the Middle East. It is typically cloned with many cultivars (over 3000). A means of accurately identifying specific clones and an understanding of the relationships among major commercial cultivars would provide valuable information for the maintenance, potentially an improvement and continued conservation of superior genotypes. Phylogenetic relationships amid commercial date cultivars are poorly understood, despite their importance. This research aimed at providing applicable knowledge through an expedient technique, by developing an exclusively tailored Simple Sequence Repeat (SSR) panel, custom-made for date palm fingerprinting and molecular identification also named as 'Dates PalmàPrinting'. This assembled modified genotyping by microsatellite markers provides a standardized approach to cultivar identification and a quality control application in date palm micropropagation production. A deeper understanding and relationship of today's major commercial cultivars is incomplete. Improving the development and productivity of this tree species is restricted due to few genetic resources. Only regionally narrowed studies have been conducted but it is more important to have a broader base of such knowledge. The present research reports on 20 selected, commercially important date palm cultivars, consisting of 18 females and 2 males, which are grown throughout the world. The knowledge of relationships among these cultivars is needed, although the date palm genome has been mostly sequenced (90.2 %) with 41,660 gene models representing an 82,354 scaffold. The relationships among the major cultivars remain unclear. Presently, the information on the characterization of these cultivars requires an assessment to better understand the relationships among the superior genotypes. The use of microsatellites, due to their accuracy and high polymorphic capability, have led to fine scaled phylogenies. The phylogenetic relationships were determined using neighbor joining un-rooted trees correlated with genetic structure clustering. Primer selections were achieved from evaluation of 14 nuclear SSR loci isolated from P. dactylifera. Results revealed a high degree of polymorphism observed in the 20 cultivars with fewer common alleles than anticipated. Within the cultivars studied, a broad heterozygosity across base pair (bp) amplification data has led to an understanding of limited inbreeding, accounting for possible adaptation to environmental changes and revealing conserved extensive array of genomic structure. Population structure analysis suggests a large genetic boundary between Northwest African and Middle Eastern cultivars with 6 subpopulations that represent divergences and fragments of admixture in cultivars present in these regions. The possible selection of potential and good quality parents is achievable for improving cultivars by generating population and structure maps. This analysis documents patterns of relationship and provides genetic structure and diversity of gene pool specificity complexes of date palm cultivars.

This study provides insights about the relationships that exist among cultivars of interest through genetic sequence analysis using SSRs, facilitating the development of a standard approach to identification and enhancements to the micropropagation process.
Keywords: microsatellites; Phoenix dactylifera L.; simple sequence repeats; phylogenetics; genetic structure; date palm; genetic diversity